Highly excited strings I: Generating function - Skliros, Dimitri P.; Copeland, Edmund J.; Saffin, Paul M. (Elsevier, 2017)
This is the first of a series of detailed papers on string amplitudes with highly excited strings (HES). In the present paper we construct a generating function for string amplitudes with generic HES vertex operators using a fixed-loop momentum formalism. We generalise the proof of the chiral splitting theorem of D'Hoker and Phong to string amplitudes with arbitrary HES vertex operators (with generic KK and winding charges, polarisation tensors and oscillators) in general toroidal compactifications E=RD−1,1×TDcr−DE=RD−1,1×TDcr−D (with generic constant Kähler and complex structure target space moduli, background Kaluza-Klein (KK) gauge fields and torsion). We adopt a novel approach that does not rely on a “reverse engineering” method to make explicit the loop momenta, thus avoiding a certain ambiguity pointed out in a recent paper by Sen, while also keeping the genus of the worldsheet generic. This approach will also be useful in discussions of quantum gravity and in particular in relation to black holes in string theory, non-locality and breakdown of local effective field theory, as well as in discussions of cosmic superstrings and their phenomenological relevance. We also discuss the manifestation of wave/particle (or rather wave/string) duality in string theory.